Cultural change through the implementation of an enterprise system: A UK university case study. Issue 5 (11th September 2017) - Skoumpopoulou, Dimitra; Waring, Teresa
Abstract : Purpose: Organisations spend a lot of money, time and resources on enterprise system (ES) implementation and often they do not realise the expected benefits from these complex systems. There is a gap in the literature in providing sufficient insight into the implementation process or how an ES might influence or contribute to a culture change. The purpose of this paper is to address the gap in the ES literature around culture by exploring the implementation that was undertaken within a large UK university. Design/methodology/approach: This paper contributes to the higher education (HE) and ES literature through an in-depth study of an ES, Strategic Information Technology Services (SITS) implementation within a university in the UK. The study was undertaken over a three-year period where one of the authors was embedded within the organisation. Findings: Using a cultural analysis framework, the extensive rich data were analysed and the outcomes indicate that SITS has had a huge influence on the culture of the university; the technology's rigid structure has imposed many changes that had not been anticipated. Originality/value: ES have recently emerged in the HE sector where they are intended to support the management of student data and provide strategic management information. Although there are many studies which have explored important aspects of the implementation of ES, one area that appears to have been under-researched is how these systems are implicated in culture change within organisations. The results of this study will enable managers as well as IT specialists to gain rich insights into an ES implementation in the HE sector and to use this knowledge for future implementations.